Structural Damage Identification Method Based on Parametric Boundary Condition Optimization - Wei Guo; Wei Jiang (Advances in Multimedia)
According to the heterogeneous background interference, the subjective consciousness, inaccurate quantification, and high cost in practical engineering, a method of applying the Bouc–Wen hysteresis nonlinear model to hysteresis characteristics of rubber isolation bearings is proposed, and this method analyzes the sensitivity of nonlinear parameters of the Bouc–Wen hysteresis model and obtains the order of nonlinear parameters of hysteresis model under different sizes of excitation. The results show that the prediction error of fatigue life is 16% less under various stress ranges, a rectangular identification frame with a certain probability guarantee rate is used to realize multitype seismic damage classification and location, the average accuracy of the identification of concrete cracking and spalling, steel bar exposure, and buckling is more than 80%, and the average coverage rate is more than 88%. During the use of civil engineering structures, the working environment is constantly changing; combined with the current damage identification and detection methods, the structure health monitoring system is established, and it is of great significance to promote the practical development of structural damage identification methods to accurately monitor the structure state in real time and to make a rapid and accurate diagnosis when the structure damage occurs.